PREVENTION AND TREATMENT OF POSTPARTUM HEMORRHAGE. WHAT DO WE KNOW ABOUT IT? NO ASSURANCES AND MUCH - Sotelo Salgueiro, Gonzalo (2015)
Postpartum hemorrhage continues as an important cause of maternal death and in developing countries is the main cause. Any patient in labor has the possibility to present this accident, but many factors supposedly increase this risk. The authors performed this review in order to establish recommendations for prevention and treatment based in the best evidences. They searched Cochrane Library, Medline, Lilacs, PubMed and Embase data bases. For recommendations on prevention and treatment they considered randomized clinical investigations or reviews. The authors consider the different existing definitions and emphasize the more than 500 mL blood loss as the most common one but whose clinical appreciation is commonly difficult. Most of the cases are due to uterine atony, placenta or fragments retention, and birth canal lacerations, and the well known associated factors, even though most pregnant women with post partum hemorrhage do not present risk factors. Different controlled clinical essays and one Cochrane systematic review indicate the best way in preventing post partum hemorrhage is either by active management of the third stage of labor with cxytocin once the anterior shoulder appears or once the baby is born, controlled cord traction, or uterine counter traction. Accidents and the need of blood transfusion have decreased with these methods. With post partum hemorrhage developing, the obstetricianshould adopt general measures including venoclysis and oxytocin use, vital functions care and then determine the bleeding cause. The specific treatment will depend on the cause.